DEVELOPING THE STUDENTS’ ABILITY IN WRITING THROUGH GUIDED QUESTIONS TECHNIQUE - Syahban Mada Ali (Universitas Muhammadiyah Enrekang, 2020)
The objective of the research is to find out the use of guide question technique effective in improving the Students’ language use and organization in writingat the secondsemester students English Education Study Program at Tomakaka University of Mamuju. This research took place at University of Tomakaka Mamuju which the researcher used pre-experimental. Population of research was the second grade students of English Education Study Program in academic year 2019/2020. Sample of the research was 25students that take by purposive sampling technique. The researcher used writing test in essay form as instrument of the research. Result of data analysis showed that t-table value at n-1 = 25-1=24 (at significant level α = 0,05) was 2.06and t-test value was 9.90. It showed t-test was higher than t-table, it meant that null hypothesis was rejected and alternative hypothesis was accepted. Therefore, the researcher summarized that the use of Guide Question technique could develop the students’language Use and Organization in writing at the second semester students of English Education Study Program at Tomakaka University of Mamuju. It was supported result of students’ mean score at pre-test and post-test. Which mean score of pre-test was 67.44(Fair score) improved to 78.36 (good score) at the post-test.